COMPARISON OF SALIVARY pH LEVEL BETWEEN DOWN SYNDROME AND NON-DOWN SYNDROME (NORMAL) PATIENTS (Case Review in Martapura, Banjar Regency) - Rudie Syahrizal Akhmad; Rosihan Adhani; Didit Aspriyanto (Universitas Lambung Mangkurat, 2019)
ABSTRACTBackground : Down syndrome is a genetic chromosomal abnormality that causes disorder in the motor, sensory and cognitive systems, also difficulty in maintaining oral hygiene to the sufferers. However, the prevalence of dental caries in Down syndrome patients is actually lower than Non-Down Syndrome individuals. This is thought to be due to the influence of the higher salivary pH of Down syndrome patients. Objective: To find out the ratio of salivary pH between people with Down Syndrome and Non-Down Syndrome individuals in Special Schools in Martapura, Banjar Regency. Methods: This study used an observational analytic method with a Cross Sectional approach. The sampling method was total sampling of all Down syndrome patients in Special Schools in Martapura, Banjar Regency and non-Down Syndrome respondents using simple random sampling, were taken randomly in elementary, middle and high school in Martapura. Measurement of salivary pH was carried out using a digital pH meter. Results: The results showed a significant difference between the salivary pH level in People with Down Syndrome and Non-Down Syndrome. The salivary pH level of Non-Down Syndrome was lower than ones with Down syndrome. The average value of the Non-Down Syndrome salivary pH level was 6.19 and Down syndrome was 7.24. Conclusion: Salivary pH of patients with Down Syndrome is higher than the Non-Down Syndrome individual which means the salivary pH in people with Down Syndrome are more alkalic than Non-Down Syndrome (Normal) individual.Keywords: Dental Caries, Down Syndrome, pH, Saliva